Powder battery binder as well as preparation method and application thereof
A pre-neutralized and post-crosslinked powder battery binder addresses the limitations of current binders by improving adhesion and reducing resistance, enhancing the electrochemical performance of lithium-ion batteries, especially with silicon-carbon electrodes.
Patent Information
- Application Number
- CN202411274586.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-12
AI Technical Summary
Current negative electrode binders for lithium-ion batteries, such as styrene-butadiene rubber (SBR) and polyacrylic acid (PAA), face challenges in meeting the demands of high energy density and low-temperature performance due to limited polar functional groups and high viscosity, leading to inadequate adhesion and volume expansion issues, especially with silicon-carbon negative electrodes.
A method involving pre-neutralization of carboxyl-containing monomers followed by reverse suspension polymerization and post-crosslinking to produce a powder battery binder with ultra-large molecular weight, using a specific solubility-based neutralization degree and a reactive dispersant to enhance bonding strength and reduce internal resistance.
The method results in a powder battery binder that improves adhesion and reduces internal resistance, facilitating better ion transmission and electrochemical performance, particularly in silicon-carbon negative electrodes, by forming a network structure and enhancing the coverage and stripping force of electrode active materials.
Smart Images

Figure BDA0005039759840000031 
Figure BDA0005039759840000071 
Figure BDA0005039759840000081
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and specifically relates to a preparation method of a powder battery binder and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in electronic products, electric vehicles, energy storage equipment and other fields due to their high energy density, long cycle life and easy design. As the application scenarios and functional requirements of various products become increasingly diverse, the market has also put forward higher requirements for the energy density, reliability and cost of lithium-ion batteries. Especially in the pursuit of high energy density lithium batteries, the demand for silicon-carbon materials is growing, and such materials have more stringent requirements for battery negative electrode adhesives.
[0003] Negative electrode binder is an important polymer material in lithium-ion batteries. Its main function is to adhere the negative electrode active material (graphite, silicon carbon, silicon, etc.) and conductive agent to the current collector. Although the amount of binder is not much (about 1.5-5% of the negative electrode material), its performance has an important impact on the performance of lithium batteries such as specific capacity, coulomb efficiency, internal resistance and cycle life.
[0004] At present, the most widely used negative electrode binder is styrene-butadiene rubber solution (SBR), which needs to be added with carboxymethyl cellulose (CMC) as a thickening dispersant during use. The composition of the materials determines that the content of polar functional groups such as carboxyl, ester and cyano contained in SBR / CMC is limited. At the same time, the interaction between negative electrode materials, especially silicon-carbon negative electrodes, is weak, so the comprehensive performance of the battery, especially the low-temperature performance, has become increasingly difficult to meet application requirements. Polyacrylic acid binders contain a high content of polar functional groups in the polymer. During the charge and discharge process, there is a complexation and decomplexation between the polar functional groups and lithium ions, which can promote lithium ion conduction and reduce the internal resistance of the battery.
[0005] In addition, polyacrylic acid binders can form hydrogen bonds with the surface of silicon negative electrode, improve the dispersion and adhesion of negative electrode materials, thereby inhibiting the volume expansion of negative electrode active materials during charging and discharging, and improving the performance of SEI film to prevent the decomposition of electrolyte during electrochemical cycling.
[0006] At present, PAA used in the industry is mainly water-based products. In order to improve its ability to inhibit volume expansion, the molecular weight of PAA is generally very large, which makes the product viscosity very high and the solid content is generally low, which greatly increases the transportation cost and use efficiency. At the same time, with the development of dry electrode technology, the demand for powder PAA has further increased. In order to achieve the preparation of powder PAA, researchers consider using solvent precipitation method. CN 117720869 A adopts the method of first precipitation polymerization and then neutralization to prepare powder. The problem of this method is that water and solvent are miscible, which affects the subsequent separation of water and solvent, and the solvent cannot be reused. The amount of three wastes generated is large. In order to solve the above problems, the present invention controls the neutralization degree of dispersant and monomer to obtain solid-liquid separation and incompatible products at one time. Powder PAA can be obtained by simple filtration and drying, which has the advantages of low energy consumption and simple preparation method. Summary of the invention
[0007] One of the purposes of the present invention is to provide a method for preparing a powder battery binder. The binder is pre-neutralized before polymerization, the binder is prepared by reverse suspension polymerization, and the excess carboxyl monomer is used for post-crosslinking modification. The prepared binder has an ultra-large molecular weight and excellent bonding strength.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] In one aspect, the present invention provides a method for preparing a powder battery binder, the method comprising the following steps:
[0010] S1: mixing the aqueous phase mixed solution and the oil phase solution and performing reverse phase suspension polymerization to obtain a suspension;
[0011] S2: post-crosslinking the suspension to obtain a modified suspension;
[0012] S3: The modified suspension is removed from the residual oil phase and water, and then dried to obtain a powder battery binder.
[0013] The aqueous phase mixed liquid in S1 contains pre-neutralized carboxyl-containing monomers, acrylamide, and acrylonitrile;
[0014] The oil phase solution in S1 comprises a dispersant and a solvent immiscible with water, wherein the dispersant comprises a reactive dispersant, and the solubility of the reactive dispersant in water is denoted as S, based on the saturated solubility of 100 g of water at 25° C. The carboxyl group-containing monomer in the aqueous phase mixture is pre-neutralized, and the neutralization degree N and the solubility S satisfy the following formula:
[0015] (1 / (40S)+0.25)*100%≤N≤(1 / (5S)+0.25)*100%; preferably (1 / (30S)+0.25)
[0016] *100%≤N≤(1 / (10S)+0.25)*100%.
[0017] The term "comprising" in the present invention means that the content is ≥20%, or ≥50%, or ≥80%, or ≥90%, or equal to 100%.
[0018] In the present invention, the carboxyl group-containing monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid and maleic acid, preferably acrylic acid and methacrylic acid.
[0019] In the present invention, the water-immiscible solvent in the oil phase solution is a petroleum hydrocarbon solvent, such as one or more of aliphatic hydrocarbons, alicyclic hydrocarbons or aromatic hydrocarbons; preferably, the aliphatic hydrocarbons are one or more of n-pentane, n-hexane, n-heptane or petroleum ether, the alicyclic hydrocarbons are one or more of cyclopentane, methylcyclopentane, cyclohexane or methylcyclohexane, and the aromatic hydrocarbons are one or more of benzene, toluene or xylene.
[0020] In the present invention, the reactive dispersant is an acrylated modified dispersant, for example, one or more of acrylated sorbitan fatty acid esters (Span 20, Span 60, Span 80, etc.), acrylated sucrose fatty acid esters (S-370, S-570, S-970, etc.), acrylated carboxymethyl cellulose, etc.
[0021] The acryl modified dispersant is a modified dispersant in the prior art, such as those described in the following references:
[0022] 1. Chen Zhengguo et al., Study on the synthesis and properties of acryloyl Span 60, Daily Chemical Industry, 1998.
[0023] 2. Wang Jinghui et al., Preparation of polymer emulsifier by esterification reaction of Span 80 with acrylic acid, Fine Chemicals, 2007.
[0024] 3. Peng Shunjin et al., Preparation of oil-soluble nonionic polymerizable surfactant ASMO, Fine Petrochemicals, 2000.
[0025] The above documents are cited as prior art in this application.
[0026] The acryl modified dispersant has the following general structural formula:
[0027]
[0028] Preferably, the amount of the reactive dispersant used is 0.05-1% of the mass of the monomers before neutralization of the aqueous phase mixture in step S1.
[0029] 5%, more preferably 0.5-3%, for example, 1.25%, 1.5%, 2%, 2.5%.
[0030] In the present invention, in step S1, the mass ratio of the petroleum hydrocarbon solvent of the oil phase solution to the aqueous phase mixed liquid is 0.1-10:1, preferably 1-5:1, for example, 1.5:1, 2.5:1.
[0031] In the present invention, the amount of carboxyl-containing monomer added accounts for 20-40wt% of the total monomer amount, the amount of acrylamide added accounts for 10-40wt% of the total monomer amount, and the amount of acrylonitrile added accounts for 40-50wt% of the total monomer amount.
[0032] In the present invention, optionally, the aqueous phase mixture further comprises a crosslinking agent; preferably, the crosslinking agent is a small molecule compound containing two or more terminal double bonds, preferably one or more of divinylbenzene, allyl methacrylate, diallyl phthalate, pentaerythritol triallyl ether, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide; preferably, the amount of the crosslinking agent added is 0-0.1wt% of the unneutralized monomer, based on the amount of the carboxyl-containing monomer.
[0033] In one embodiment of the present invention, the aqueous phase mixture in S1 further comprises an initiator, which is a water-soluble thermal initiator and / or an oxidation-reduction initiator. Preferably, the initiator is one or more of ammonium sulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, hydrogen peroxide, isoascorbic acid, sodium pyrosulfite and sodium bisulfite.
[0034] In one embodiment of the present invention, a neutralizing agent is added to the carboxyl group-containing monomer in S1 for pre-neutralization; preferably, the neutralizing agent is an inorganic alkali metal hydroxide, preferably one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate, and potassium carbonate.
[0035] In one embodiment of the present invention, the post-crosslinking agent treated with the post-crosslinking agent described in S2 is a polyglycidyl ether, selected from one or more of ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and allyl glycidyl ether. Calculated on the basis of the carboxyl-containing monomer, the amount of the post-crosslinking agent added is 0.01-1wt% of the unneutralized monomer, preferably 0.1-0.8wt%, such as 0.3wt%, 0.5wt%.
[0036] In one embodiment of the present invention, in the step of removing the residual oil phase and water described in S3, the solvent and water form an azeotrope, the removal temperature is 80-150°C, such as 90°C, 110°C, 140°C, and the amount of water removed is 50-95% of the amount of water added; drying adopts one of air drying or fluidized bed drying, the drying temperature is 80-150°C, and the time is 0.5-2h.
[0037] Another object of the present invention is to provide a powder battery binder.
[0038] Another object of the present invention is to provide a use of a powder battery binder.
[0039] A use of a powder battery binder, wherein the binder is a binder prepared by the above-mentioned preparation method, or is the above-mentioned binder, and the powder battery binder is used for positive and negative electrodes of lithium-ion batteries.
[0040] Another object of the present invention is to provide a positive and negative electrode of a lithium ion battery, which comprises a powder battery binder.
[0041] The negative electrode is artificial graphite, natural graphite, hard carbon, silicon carbon, and the positive electrode is ternary, lithium cobalt oxide, lithium iron phosphate, and lithium manganese oxide.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The powder battery binder of the present invention uses a reverse suspension process and provides an ion transmission channel through pre-neutralization to effectively improve the electrochemical performance of the lithium ion battery, wherein the degree of pre-neutralization is determined according to the solubility of the dispersant in water. When the solubility of the dispersant in water is relatively high, the degree of neutralization needs to be appropriately reduced to form effectively encapsulated microspheres and form a good oil-water interface; when the solubility of the dispersant in water is relatively low, the degree of neutralization needs to be appropriately increased, and the dispersant can be interlaced and encapsulated by means of strong charge repulsion to avoid the undesirable situation of oil phase polymerization.
[0044] By post-crosslinking the reserved carboxyl groups with polyglycidyl ether, the fibrillation of the binder in the dry electrode can be facilitated to form a network structure, thereby improving the coverage and stripping force of the electrode active material and reducing the internal resistance of the battery. DETAILED DESCRIPTION
[0045] The present invention will be further described below through specific embodiments. The specific embodiments are only detailed descriptions of the contents of the present invention, but not limiting the scope of the present invention.
[0046] The synthesis method of the reactive dispersant involved in the embodiment of the present invention refers to the following documents:
[0047] 1. Chen Zhengguo et al., Study on the synthesis and properties of acryloyl Span 60, Daily Chemical Industry, 1998.
[0048] 2. Wang Jinghui et al., Preparation of polymer emulsifier by esterification reaction of Span 80 with acrylic acid, Fine Chemicals, 2007.
[0049] 3. Peng Shunjin et al., Preparation of oil-soluble nonionic polymerizable surfactant ASMO, Fine Petrochemicals, 2000.
[0050] The preparation method of acryloyl sucrose fatty acid ester (S-370, solubility 0.4g / 100g water) is as follows:
[0051] Weigh 250g sucrose fatty acid ester, 14.4g acrylic acid, 1.3g p-toluenesulfonic acid (catalyst), and 1.3g hydroquinone (inhibitor) into a four-necked flask containing 300mL n-heptane (solvent), stir and reflux at 108°C for 20h. At this time, the water output in the water separator is about 2.8g, and the esterification rate is about 80% after calculation. Then, filter while hot, wash the filtrate with 0.1% NaOH until the pH of the water phase is about 6, and then wash with pure water until the pH is about 7, separate the water phase, and distill the oil phase to remove the solvent under reduced pressure to obtain a crude product, purify the crude product with ethyl acetate, and vacuum dry to obtain a fine product.
[0052] The preparation method of acryloyl sodium carboxymethyl cellulose (CMC1) (solubility 2g / 100g water) is as follows:
[0053] Weigh 100g sodium carboxymethyl cellulose (brand MAC500LC, Nippon Paper), 14.4g acrylic acid, 1.3g p-toluenesulfonic acid (catalyst), 1.3g hydroquinone (inhibitor) into a four-necked flask containing 150mL toluene (solvent), stir and reflux for 15h at 118℃. At this time, the water output in the water separator is about 3.0g, and the esterification rate is about 83% after calculation. Then, filter while hot, wash the filtrate with 0.1% NaOH until the pH of the water phase is about 6, then wash with pure water until the pH is about 7, separate the water phase, and distill the oil phase to remove the solvent under reduced pressure to obtain a crude product, purify the crude product with ethyl acetate, and vacuum dry to obtain a fine product.
[0054] The preparation method of acrylated sodium carboxymethyl cellulose (CMC2) (solubility 7g / 100g water) is as follows:
[0055] Weigh 80g sodium carboxymethyl cellulose (brand BH2000, Changshu Weiyi), 14.4g acrylic acid, 1.3g p-toluenesulfonic acid (catalyst), 1.3g hydroquinone (inhibitor) into a four-necked flask containing 150mL toluene (solvent), stir and reflux for 15h at 118℃. At this time, the water output in the water separator is about 3.0g, and the esterification rate is about 83% after calculation. Then, filter while hot, wash the filtrate with 0.1% NaOH until the pH of the water phase is about 6, then wash with pure water until the pH is about 7, separate the water phase, and distill the oil phase to remove the solvent under reduced pressure to obtain a crude product, purify the crude product with ethyl acetate, and vacuum dry to obtain a fine product.
[0056] The preparation method of acrylated sodium carboxymethyl cellulose (CMC3) (solubility 7g / 100g water) is as follows:
[0057] Weigh 92g sodium carboxymethyl cellulose (brand MAC350, Nippon Paper), 14.4g acrylic acid, 1.3g p-toluenesulfonic acid (catalyst), and 1.3g hydroquinone (inhibitor) into a four-necked flask containing 150mL toluene (solvent), stir and reflux for 15h at 118°C. At this time, the water output in the water separator is about 3.0g, and the esterification rate is about 83% after calculation. Then, filter while hot, wash the filtrate with 0.1% NaOH until the pH of the water phase is about 6, and then wash with pure water until the pH is about 7, separate the water phase, and distill the oil phase to remove the solvent under reduced pressure to obtain a crude product, which is purified with ethyl acetate and vacuum dried to obtain a fine product.
[0058] The preparation method of acryloyl sorbitan fatty acid ester (Span 60, solubility 0.2g / 100g water) is as follows:
[0059] Weigh 190g of sorbitan fatty acid ester, 14.4g of acrylic acid, 1.3g of p-toluenesulfonic acid (catalyst), and 1.3g of hydroquinone (inhibitor) into a four-necked flask containing 150mL of toluene (solvent), stir and reflux for 15h at 118°C. At this time, the water output in the water separator is about 3.0g, and the esterification rate is about 83% after calculation. Then, filter while hot, wash the filtrate with 0.1% NaOH until the pH of the water phase is about 6, and then wash with pure water until the pH is about 7, separate the water phase, and distill the oil phase to remove the solvent under reduced pressure to obtain a crude product, which is purified with ethyl acetate and vacuum dried to obtain a fine product.
[0060] The preparation method of acryloyl sorbitan fatty acid ester (Span 80, solubility 0.5g / 100g water) is as follows:
[0061] Weigh 205g of sorbitan fatty acid ester, 14.4g of acrylic acid, 1.3g of p-toluenesulfonic acid (catalyst), and 1.3g of hydroquinone (inhibitor) into a four-necked flask containing 150mL of toluene (solvent), stir and reflux for 15h at 118°C. At this time, the water output in the water separator is about 3.0g, and the esterification rate is about 83% after calculation. Then, filter while hot, wash the filtrate with 0.1% NaOH until the pH of the water phase is about 6, and then wash with pure water until the pH is about 7, separate the water phase, and distill the oil phase to remove the solvent under reduced pressure to obtain a crude product, purify the crude product with ethyl acetate, and vacuum dry to obtain a fine product.
[0062] The main raw materials and their sources used in the examples and comparative examples are shown in Table 1:
[0063] Table 1 Main raw materials and sources for preparing solution type adhesives
[0064] Abbreviations Compound Manufacturer AA acrylic acid Wanhua Chemical Group Co., Ltd. MAA Methacrylic acid Wanhua Chemical Group Co., Ltd. AN Acrylonitrile Wanhua Chemical Group Co., Ltd. AM Acrylamide Wanhua Chemical Group Co., Ltd. MBA N,N-Methylenebisacrylamide Jinan Noshi New Materials Co., Ltd. PEGDA 400 Polyethylene glycol 400 diacrylate Sinopharm Group SPS Sodium Persulfate Unified Initiator Hefei Co., Ltd. KPS Potassium Persulfate Unified Initiator Hefei Co., Ltd. <![CDATA[Na2S2O5]]> Sodium metabisulfite Wanhua Chemical Group Co., Ltd. n-Heptane n-Heptane Sinopharm Group n-Hexane n-Hexane Sinopharm Group Ethylene glycol diglycidyl ether Ethylene glycol diglycidyl ether Anhui Hengyuan Butanediol diglycidyl ether Butanediol diglycidyl ether Anhui Hengyuan
[0065] Unless otherwise specified, other chemical reagents used in the examples were purchased from the market and were of analytical grade.
[0066] Example 1
[0067] 500 g of n-heptane was added to a 2 L four-necked separable flask equipped with a stirrer, a reflux condenser, a thermometer and a nitrogen inlet tube. 0.92 g of acryloyl-modified Span 60 (a reactive dispersant, prepared according to Reference 1) was added thereto, the temperature was raised to 80° C. and the mixture was uniformly dissolved and dispersed at a stirring speed of 400 rpm, and then the temperature was lowered to 50° C. This was an oil phase solution.
[0068] 124g of acrylic acid was added to a 1L conical flask, and 140g of a 32% sodium hydroxide aqueous solution was added dropwise to the conical flask while cooling to below 45°C. Then 50g of acrylamide, 140g of acrylonitrile, 0.368g of potassium persulfate, 0.184g of polyethylene glycol 400 diacrylate (PEGDA400) and 172g of deionized water were added thereto, and stirred and mixed uniformly to obtain an aqueous phase mixture.
[0069] Half of the aqueous phase mixture was added to a four-necked flask, and nitrogen was introduced for 30 minutes while stirring at a stirring speed of 400 rpm. The temperature was then raised to 80° C. for 1 hour for polymerization reaction to obtain a polymer suspension.
[0070] The temperature was raised to 95°C, and 0.2 g of ethylene glycol diglycidyl ether was added to the polymerized suspension and the reaction was continued for 2 h to obtain a modified suspension. The system was filtered and centrifuged to remove the residual n-heptane and water, and finally dried at 150°C for 40 min to obtain a powdered battery binder.
[0071] Example 2
[0072] The amounts of the raw materials used in Examples 2-6 and Comparative Examples 1-4 are shown in Table 2.
[0073] Table 2 Amount of each raw material
[0074]
[0075] Table 3 Neutralization degree and dispersant solubility of examples and comparative examples
[0076] Group Neutralization degree N Solubility Whether the restrictions are met Example 1 65 0.2 yes Example 2 30 2 yes Example 3 25 7 yes Example 4 49 0.4 yes Example 5 42 0.5 yes Example 6 28 3 yes Comparative Example 1 0 0.2 no Comparative Example 2 83 0.2 no Comparative Example 3 56 0.2 yes
[0077] Test method:
[0078] The solubility test method is as follows: weigh 100g of deionized water at a constant temperature of 25°C, and continuously add the reactive dispersant to the water under stirring. As the amount added increases, the viscosity of the aqueous solution of the dissolved reactive dispersant begins to increase until it is fully stirred (4h), and particle agglomerates of the reactive dispersant that cannot be dispersed appear in the aqueous solution. At this time, the saturated solubility of the reactive dispersant is reached, that is, the solubility of the reactive dispersant at 25°C.
[0079] The powdered battery binder prepared in the embodiment and the comparative example is applied to the preparation of the negative electrode sheet of a lithium ion battery, and the steps are as follows:
[0080] At room temperature, 1 part of conductive carbon black sp and 97.2 parts of negative electrode active material (graphite) were added to a stirring tank and mixed, and then 1.8 parts of powdered battery binder were added. External high shear force was applied to the dry mixture to fibrillate the battery binder and bond the electrode membrane powder. Finally, the mixture was extruded to form a self-supporting film.
[0081] The peel strength and electrochemical performance of the prepared negative electrode sheets were evaluated.
[0082] Peel strength evaluation: It is tested by a special adhesion tester. The test method of peel strength refers to the American Society for Testing and Materials standard ASTM D3330. The instrument is a Kejian tensile testing machine. The details are as follows: Cut the negative electrode into a 150mm long and 15mm wide electrode along the rolling direction. Stick a 3M double-sided tape with a length of 100mm and a width of 15mm on a smooth stainless steel plate, stick the electrode flat on the double-sided tape, roll it back and forth 10 times with a 2kg rubber roller, and then fix the stainless steel plate on the tensile machine. The electrode that is not attached to the tape is reversely clamped on the tensile machine probe. The base of the tensile machine pulls the electrode at a speed of 5cm / min, and the sensor measures the peeling force during the process. The average value of each group of 5 parallel samples is the final peel strength.
[0083] Peel force = computer reading / 0.015, unit: N / m.
[0084] Electrochemical performance evaluation: The prepared negative electrode plate and the positive electrode plate with lithium iron phosphate as the positive electrode material are prepared and assembled into an aluminum-plastic flexible package according to the lithium-ion battery production process familiar to technicians in this industry, and the electrochemical performance test is carried out.
[0085] The details are as follows:
[0086] Determination of 1000 cycle capacity retention rate: At 25°C, 3.5V voltage range, 0.5C charging, 1.0C discharging for charge and discharge cycles, constant current method to test its capacity retention rate after 1000 cycles, capacity retention rate = 1000th cycle discharge gram capacity / 1st cycle discharge gram capacity.
[0087] Diaphragm resistance test method: Cut the 20cm long negative electrode after rolling, randomly select 10 points on the coating area of the electrode, and measure the resistance value at these points with a four-probe diaphragm resistance meter. The average of the 10 values is the final diaphragm resistance value. Instrument: ACCFILM four-probe diaphragm resistance tester TT-ACCF-G2A.
[0088] Table 5 Electrochemical performance data
[0089]
[0090]
[0091] From the performance results in the table, it can be seen that Examples 1 to 6 all have higher peeling force, lower membrane resistance, better fiberization and filamentation, and excellent cycle capacity retention. In comparison group 1, no pre-neutralization was performed, and the electrostatic repulsion was insufficient, resulting in a decrease in ion conductivity and a significant increase in membrane resistance. After neutralization, comparison group 2 was over-neutralized, resulting in insufficient post-crosslinking efficiency and failure to fiberize. Comparison group 3 showed that no post-crosslinking agent would also result in failure to fiberize, further demonstrating the importance and necessity of post-crosslinking.
[0092] The above description is only a specific description of the preferred embodiment of the present invention, and is not intended to limit the scope of protection of the present invention. It should be noted that a person skilled in the art may make several improvements and supplements based on the technical solution of the present invention, and these improvements and supplements should all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a powder battery binder, the method comprising the following steps: S1: mixing the aqueous phase mixed solution and the oil phase solution and performing reverse phase suspension polymerization to obtain a suspension; S2: post-crosslinking the suspension to obtain a modified suspension; S3: removing the residual oil phase and water from the modified suspension, and then drying to obtain a powder battery binder; The aqueous phase mixed liquid in S1 contains pre-neutralized carboxyl-containing monomers, acrylamide, and acrylonitrile; The oil phase solution in S1 comprises a dispersant and a solvent immiscible with water, wherein the dispersant comprises a reactive dispersant, and the solubility of the reactive dispersant in water is denoted as S, based on the saturated solubility of 100 g of water at 25° C. The carboxyl group-containing monomer in the aqueous phase mixture is pre-neutralized, and the neutralization degree N and the solubility S satisfy the following formula: (1 / (40S)+0.25)*100%≤N≤(1 / (5S)+0.25)*100%; preferably (1 / (30S)+0.25)*100%≤N≤(1 / (10S)+0.25)*100%.
2. The preparation method according to claim 1, characterized in that The carboxyl group-containing monomer is selected from one or more of acrylic acid, methacrylic acid, itaconic acid, crotonic acid, fumaric acid and maleic acid, preferably acrylic acid and methacrylic acid.
3. The preparation method according to claim 1 or 2, characterized in that: The water-immiscible solvent in the oil phase solution is a petroleum hydrocarbon solvent, such as one or more of aliphatic hydrocarbons, alicyclic hydrocarbons or aromatic hydrocarbons; preferably, the aliphatic hydrocarbons are one or more of n-pentane, n-hexane, n-heptane or petroleum ether, the alicyclic hydrocarbons are one or more of cyclopentane, methylcyclopentane, cyclohexane or methylcyclohexane, and the aromatic hydrocarbons are one or more of benzene, toluene or xylene.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The reactive dispersant is an acryloyl modified dispersant, for example, one or more of acryloyl sorbitan fatty acid esters (Span 20, Span 60, Span 80, etc.), acryloyl sucrose fatty acid esters (S-370, S-570, S-970, etc.), acryloyl carboxymethyl cellulose, etc., preferably an acryloyl modified dispersant with the following general structural formula:
5. The preparation method according to any one of claims 1 to 4, characterized in that: The amount of the reactive dispersant is 0.05-5% of the mass of the monomers before neutralization of the aqueous phase mixture in step S1, and more preferably 0.5-3%; and / or, the mass ratio of the petroleum hydrocarbon solvent of the oil phase solution to the aqueous phase mixture is 0.1-10:1, and preferably 1-5:1; and / or, the amount of carboxyl-containing monomer added accounts for 20-40wt% of the total amount of monomers, the amount of acrylamide added accounts for 10-40wt% of the total amount of monomers, and the amount of acrylonitrile added accounts for 40-50wt% of the total amount of monomers.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The aqueous phase mixture further comprises a crosslinking agent; preferably, the crosslinking agent is a small molecule compound containing two or more terminal double bonds, preferably one or more of divinylbenzene, allyl methacrylate, diallyl phthalate, pentaerythritol triallyl ether, ethylene glycol dimethacrylate, and N,N-methylenebisacrylamide; preferably, the amount of the crosslinking agent added is 0-0.1wt% of the unneutralized monomer, based on the amount of the carboxyl-containing monomer.
7. The preparation method according to any one of claims 1 to 6, characterized in that: S1 The aqueous phase mixture also contains an initiator, which is a water-soluble thermal initiator and / or an oxidation-reduction initiator. Preferably, the initiator is one or more of ammonium sulfate, sodium persulfate, potassium persulfate, tert-butyl hydroperoxide, hydrogen peroxide, isoascorbic acid, sodium pyrosulfite and sodium bisulfite.
8. The preparation method according to any one of claims 1 to 7, characterized in that: A neutralizing agent is added to the carboxyl-containing monomer in S1 for pre-neutralization; preferably, the neutralizing agent is an inorganic alkali metal hydroxide, preferably one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate, and potassium carbonate; and / or, the post-crosslinking agent treated with the post-crosslinking agent in S2 is a polyglycidyl ether, selected from one or more of ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and allyl glycidyl ether, calculated on the basis of the carboxyl-containing monomer, the amount of the post-crosslinking agent added is 0.01-1wt%, preferably 0.1-0.8wt%, of the unneutralized monomer.
9. A powder battery binder prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the powder battery binder prepared by the preparation method according to any one of claims 1 to 8 or the powder battery binder according to claim 9 as a positive or negative electrode binder for lithium ion batteries.
Citation Information
Patent Citations
Binder for secondary battery electrode, composition for secondary battery electrode mixture layer, secondary battery electrode, and secondary battery
CN114514639A
Binder for lithium-sulfur secondary battery electrode and use thereof
CN116710492A
Method for producing slurry composition for secondary battery electrode, secondary battery electrode, and method for producing secondary battery
CN117751462A
Binder composition for secondary battery, ceramic separator, and secondary battery
CN117965111A
Cited By
High-molecular-weight negative electrode binder, preparation method thereof and negative electrode slurry
CN120737769A
